Ion Pairs for Transdermal and Dermal Drug Delivery: A Review - Mignon Cristofoli; Chin-Ping Kung; Jonathan Hadgraft; Majella E. Lane; Bruno C. Sil (MDPI AG, 2021)
Ion pairing is a strategy used to increase the permeation of topically applied ionised drugs. Formation occurs when the electrostatic energy of attraction between oppositely charged ions exceeds their mean thermal energy, making it possible for them to draw together and attain a critical distance. These ions then behave as a neutral species, allowing them to partition more readily into a lipid environment. Partition coefficient studies may be used to determine the potential of ions to pair and partition into an organic phase but cannot be relied upon to predict flux. Early researchers indicated that temperature, size of ions and dielectric constant of the solvent system all contributed to the formation of ion pairs. While size is important, this may be outweighed by improved lipophilicity of the counter ion due to increased length of the carbon chain. Organic counter ions are more effective than inorganic moieties in forming ion pairs. In addition to being used to increase permeation, ion pairs have been used to control and even prevent permeation of the active ingredient. They have also been used to stabilise solid lipid nanoparticle formulations. Ion pairs have been used in conjunction with permeation enhancers, and permeation enhancers have been used as counter ions in ion pairing. This review attempts to show the various ways in which ion pairs have been used in drug delivery via the skin. It also endeavours to extract and consolidate common approaches in order to inform future formulations for topical and transdermal delivery.